Geriatric Medicine A Problem-Based Approach (Springer Singapore, 2018)
Written by international experts, this book presents chapters that cover common geriatric conditions including dementia, depression, delirium, falls, polypharmacy, incontinence, immobility, and medication-related issues, as well as neurological, cardiovascular, and endocrine diseases associated with old age. The book also discusses various aspects of ambulatory, residential, and palliative care for the elderly, in addition to ethical aspects of old age care, advance care planning and living wills. Geriatric medicine is a rapidly growing field in internal medicine. The majority of elderly people now live in developing countries, where there is an urgent need to up-skill healthcare professionals. By presenting problems as they arise and then discussing how to solve them, this book offers a valuable resource for all physicians interested in the care of older people.